CONSUMER LEGAL EFFORTS DUE TO ABUSE OF CIRCUMSTANCES (MISBRUIK VAN OMSTANDIGHEDEN) IN STANDARDIZED AGREEMENTS - Celina Tri Siwi Kristiyani (Warmadewa Press, 2020)
Private law develops with the dynamics of community needs. Law Number 8 of 1999 concerning Consumer Protection Law is a form of regulation aimed at balancing the rights and obligations of both consumers and business actors. But in reality, consumers are always the weaker party; the injured party is due to a more inferior position. The form of consumer losses that often occur is the existence of standardized agreements containing elements of misuse (misbruik van omstanddigheden). As a result, the consumers agree not to an agreement in